Early parent–child relationships and risk of mood disorder in a Canadian sample of offspring of a parent with bipolar disorder: findings from a 16‐year prospective cohort study. Issue 5 (30th October 2014) - Doucette, Sarah; Levy, Adrian; Flowerdew, Gordon; Horrocks, Julie; Grof, Paul; Ellenbogen, Mark; Duffy, Anne
Abstract: Aim: Exposure to parental bipolar disorder (BD) early in life may increase the risk of developing a mood disorder. However, the impact of early parent–child relationships when a parent is affected and how this impacts an offspring's risk remains unclear. The primary objective of this study was to determine the association between parent–child relationships and risk of mood disorder in offspring of parents with BD and, secondly, to determine the interaction of temperament and life stress on this association. Methods: Two hundred and thirty‐three offspring completed annual clinical assessments following Kiddie Schedule for Affective Disorders (KSADS) format interviews as part of an ongoing Canadian prospective cohort study conducted from 1996 to 2013. Offspring completed measures of early adversity, life stress and temperament. Clinical data from the affected parents were prospectively collected over the first decade of their offspring's life using SADS format interviews. Results: Higher perceived neglect from mother and offspring emotionality were significantly associated with the hazard of mood disorder (hazard ratio (HR): 1.1, 95% confidence interval (CI): 1.0–1.2 and HR: 1.7, 95% CI: 1.0–3.1, respectively). Duration of exposure to parental BD significantly interacted with offspring emotionality to predict mood disorder ( P  = 0.01). Further, perceived neglect from mother was associated with offspring high emotionality ( P  = 0.02). Conclusions: Neglect from mother is a significant early predictor of mood disorder in offspring at familial risk for BD and may increase emotional sensitivity. Psychosocial support and interventions for high‐risk families could be beneficial in reducing early adversity, maternal neglect and the risk of subsequent mood disorders in offspring.